Synthesis of pyramidal, cubical and truncated octahedral magnetite nanocrystals by controlling reaction heating rate - Zhang, L.; Li, Qin; Liu, Shaomin; Ang, Ha Ming; Tade, Moses; Gu, H. (Elsevier, 2011)
Pyramidal, cubical and truncated octahedral magnetite nanocrystals have been synthesized by thermal de-composition of iron (III) acetylacetone (Fe(acac)3) in the presence of oleic acid under various reaction rate controlled by heating rate. The magnetite nanocrystals were characterized by transmission electron microscopy (TEM) and X-ray diffraction (XRD). High-resolution transmission electron microscopy (HRTEM) was applied to reveal the structural information of single magnetite (Fe3O4) nanocrystals. Magnetization curves of the three types of magnetite nanocrystals show that the pyramidal crystals exhibit a slight hysteresis compared to the other two despite of the similar size range. The results suggest that in addition to the surfactant selective capping and varying reaction temperature, the reaction rate variation is also an effective means for controlling the morphology and functions of the magnetite nanocrystals.